The Islamic Educational Values in The Serat Kabanti “Bula Malino” Composed by The 29th Sultan Of Buton - Hidayatulloh, M. Said; Pamungkas, Achmad Jumeri (Universitas Islam Sultan Agung, 2025)
The arrival of Islam in Buton gave birth to a form of integration between Islamic teachings and local wisdom, reflected in the religious literary tradition. One important representation of this process is Kabanti Bula Malino by Sultan Muhammad Idrus Kaimuddin Ibnu Badaruddin Al-Buthuni (1824–1851), a sultan and cleric who played a role in the formation of Islamic culture in Buton. This article aims to examine the Islamic educational values contained in Kabanti Bula Malino and explain the position of kabanti as a medium of education based on local culture. This study uses a qualitative approach with library research. The primary data source is the text of Kabanti Bula Malino, while secondary data sources include books, journal articles, and relevant previous research. Data analysis is carried out using a semiotic and hermeneutic approach to interpret the symbols, language, and meaning of Islamic educational values contained in the text. The research results show that Kabanti Bula Malino contains Islamic educational values, including awareness of death, purification of the soul (tazkiyatun nafs), asceticism toward the world, and ethical leadership. These values are conveyed through the local Wolio language with Pegon Arabic script, so that Islamic teachings can be understood contextually by the Butonese people. Thus, Kabanti Bula Malino functions not only as a religious literary work, but also as a medium for Islamic education that plays a role in character formation, preserving local wisdom, and strengthening the Islamic identity of the Butonese people.